Efektivitas LMS Terhadap Peningkatan Pemahaman dan Keterampilan Berpikir Kritis Siswa Pada Materi Sistem Kontrol dan Automasi - Nandito Fernandes Hornay; Agus Efendi; Deny Tri Ardianto (Jurnal Ilmiah Global Education, 2026)
The Learning Management System (LMS) is a digital-based learning management platform used to plan, implement, and evaluate the teaching and learning process online. This study aims to analyze the effectiveness of the Learning Management System (LMS) in improving students’ conceptual understanding and critical thinking skills on the topic of Control and Automation Systems at ESTV-GTI Becora School, Timor-Leste. This research is a development study (Research and Development) using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of two groups: an experimental class using an LMS based on instructional design principles and a control class using conventional methods. Data were collected through pretests, posttests, and an LMS effectiveness survey involving 65 respondents. The research results showed that the LMS achieved a high level of effectiveness, with an N-Gain score of 0.76 and an instrument reliability coefficient of 0.771 (high category). Furthermore, 96.94% of respondents expressed a positive response toward the use of LMS in learning. These findings confirm that the LMS can create an interactive and adaptive learning environment while significantly enhancing students’ critical thinking abilities and conceptual understanding.